Effectiveness of Nigella sativa Addition against TNF-Alpha in Stage III and IV Breast Cancer Undergoing Doxorubicin and Cyclophosphamide Chemotherapy at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Friyoga Syahril; Wirdah, Aisyah; Nur Qodir; Irfanuddin; Irsan Saleh; Yenny Dian Andayani; Mediarty; Norman Djamaluddin (HM Publisher, 2024)
Background: Breast cancer is a malignancy caused by the continuous uncontrolled growth of the component cells of the ducts or lobules of the breast gland. Globally, breast cancer is the second leading cause of death in women. Nigella sativa contains substances thymoquinone. Thymoquinone can inhibit the progression of cancer through anti-inflammatory, anti-oxidant mechanisms, inhibit proliferation, trigger apoptosis, and prevent angiogenesis. Chronic inflammation in breast cancer is mediated by one of them is TNF-alpha tumors. Elevated levels of TNF-α have a significant association with poor prognosis and progression of breast cancer. This study aims to determine the effectiveness of the additional Nigella sativa in declining TNF-α levels in breast cancer patients at Dr. Mohammad Hoesin General Hospital Palembang. Methods: This research used a randomized, open clinical trial design, which was carried out at the internal medicine hematology-oncology medical polyclinic and the surgical oncology polyclinic of Dr. Mohammad Hoesin General Hospital Palembang from January 2023 to October 2023. Data processing for data analysis used SPSS version 26 for Windows. Results: There were 36 research subjects followed during the study period and received Doxorubicin chemotherapy and cyclophosphamide (AC), which were divided into treatment groups of 18 people (chemotherapy with the addition of Nigella sativa @600 mg 2x2 capsule/ day and a control group of 18 people. A TNF-alpha examination was carried out before and after to assess the comparison before and after. From the results, it was found that TNF-alpha levels in the treatment group showed a decrease in TNF-alpha with a p-value <0.001. Conclusion: The addition of Nigella sativa has the effect of reducing TNF-alpha in breast cancer patients receiving AC chemotherapy at Dr. Mohammad Hoesin General Hospital, Palembang.